Increase in Road Transport Safety - Way to Reduction of External Costs - Kalasova, Alica (Communications - Scientific letters of the University of Zilina, 2005)
Satellite navigation and prepared navigation system Galileo is the key technology that has to open the gate to new applications. It has to ensure Europe to not be too dependent (in term of economic and safety) on nonmember states of EU, to establish new applications and create new markets with integrated navigation and communication services. In our article we will deal with the opportunities that the new navigation system Galileo will offer for the road transport.